Identification and Control of Transportation Units with Sequenced Learning Models Using Neural Networks - Selvarajan, Shitharth; Manoharan, Hariprasath; Saleem, Farrukh; Ramesh, S; Manikandan, T (Recent Patents on Engineering, 2024)
<span class=
Keywords: adeptness rate